Enhancement radiative cooling performance of nanoparticle crystal via oxidation. (March 2018) - Jia, Zi-Xun; Shuai, Yong; Li, Meng; Guo, Yanmin; Tan, He-ping
Highlights: Absorption performance of monolayer nanoparticle crystal has been enhanced via oxidation. Magnetic polariton and surface plasmon polariton have been excited in the structure with oxidation. Three different oxidation patterns have been discussed, and the mechanism for absorption enhancement are similar for all three cases. Coupling oscillator model and dispersion relationship of surface plasmon polariton have been employed to elucidate the physics. Abstract: Nanoparticle-crystal is a promising candidate for large scale metamaterial fabrication. However, in radiative cooling application, the maximum blackbody radiation wavelength locates far from metal's plasmon wavelength. In this paper, it will be shown if the metallic nanoparticle crystal can be properly oxidized, the absorption performance within room temperature blackbody radiation spectrum can be improved. Magnetic polariton and surface plasmon polariton have been explained for the mechanism of absorption improvement. Three different oxidation patterns have been investigated in this paper, and the results show they share a similar enhancing mechanism.